SA 8000 as a Tool for a Sustainable Development Strategy - Santos, Gilberto (2017)
ABSTRACT In today’s global markets, issues related to environmental sustainability, ethics, working environment conditions and safety, stakeholders’ relations and the protection of workers’ rights have greater importance on business performances. For this reason, the aim of this research is to analyze the concept of corporate social responsibility, investigating the perception of Italian companies about Social Accountability 8000, a voluntary International Standard used as a tool to certify companies’ commitment on social aspects. The survey began September 15, 2016 and answers were accepted until November 15, 2016. Two hundred twenty-one Italian SA8000 certified companies participated to the survey reaching a response rate of 20.4%. Using a questionnaire submitted to certified companies, the main reasons which have driven companies to certification have been investigated, highlighting that the motivations which drive companies to be certified are both of an internal and external type: an improved image is the first, followed by the willingness to have a better working environment. Among the experienced benefits resulted from the study there are ‘reduction of labor conflicts’ and ‘achievement of a competitive advantage over competitors’, while limitations seem to be scarcely perceived and are defined especially by the lack of staff and management training. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment